Refleksi Spiritual sebagai Instrumen Evaluasi dalam Pembelajaran PAI berbasis Deep Learning - Ayu Ardya Putri; Lubna; Mukhlis (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Evaluation in Islamic Religious Education (PAI) has predominantly focused on cognitive aspects, resulting in limited measurement of students’ affective and spiritual dimensions. This article aims to examine spiritual reflection as an evaluation instrument in Deep Learning–based PAI. This study employs a library research approach by analyzing relevant literature on Deep Learning, spiritual reflection, and evaluation in Islamic education. The findings indicate that spiritual reflection can be operationalized as an authentic and formative assessment tool to evaluate the internalization of religious values among students. The implementation of reflective evaluation can be carried out through various techniques, such as reflective journals, reflective discussions, muhasabah (self-introspection), spiritual portfolios, and the use of digital media. Thus, spiritual reflection functions not only as a learning strategy but also as an evaluative approach that supports the development of a more comprehensive and sustainable PAI evaluation system.